'You can hear wholly only if you remove the waxes in your ears': The Hararghe Oromo's theory for establishing the intersubjective foundation of cognition. (March 2019) - Hussein, Jeylan W
The article sets out to examine the way the Hararghe Oromo in Ethiopia use their mirriiysa culture to express and cultivate criticality, mindfulness, interpersonal sensitivity and emotional intelligence. The paper discusses the nature of the performance culture and analyses the social psychological meanings of a set of mirriiysa texts collected from a group of folk performers who participated also in the interpretation and analysis of the cultural, social and psychological meanings of the texts. For theory, the study drew on interpretivism. During data analysis, the horizontal and vertical planes of analysis interacted and reinforced each other. The act of removing earwax symbolizes a cultural dimension of intersubjectivity and interaffectivity. The analyses indicated that mirriiysa is a socio-cultural performance wherein listening, understanding and responding occur in socially meaningful and interactive contexts. To understand the communicative intent of a mirriiysa text, one should take broader perspectives and pay due attention to the non-linguistic elements that offer the performance holistic import. The paper highlights the implication of these and other findings for our understanding of the meanings of mirriiysa and other genre performances.